Censorship: Social media, including X/Twitter, Facebook, Instagram and Y (Pakistan) - Voidly (2024)
WARNING severity censorship detected in Pakistan. Confidence: 75%. Data sourced from CensoredPlanet.
Censorship Incident ID: PK-2024-0002
Keywords: censorship; PK; censorship; warning